Social Sciences Laboratory: Between Reality and Expectation in Improving the Quality of Learning in Schools - Lutfaidah, Anna; Sarmini, Sarmini; Purnomo, Nugroho Hari (International Journal for Educational and Vocational Studies, 2020)
Social studies learning by utilizing laboratories will make it easier for students to construct concepts and understand the material being taught. The existence of a relatively recently developed social studies laboratory is interesting to study so that it can become a reference for the next development stage. This research is a descriptive qualitative research that the role of social studies laboratories has been used by teachers in improving the quality of learning in schools. Data retrieval is done by interviews, questionnaires and observations Data analysis techniques in research using qualitative analysis is done by reflecting the results of observations of the learning process carried out. Data in the form of words from field notes are processed into meaningful sentences and analyzed qualitatively. IPS Laboratory is able to facilitate understanding, increase students' curiosity. However, this has not been optimal due to several things such as the unavailability of laboratory rooms, the systematic use of social studies laboratories, the lack of procedures for the use of complete IPS laboratories, and problems with facilities and infrastructure that have not been supported.